Music Listening in Times of COVID-19 Outbreak: A Brazilian Study - Ribeiro, Fabiana Silva; Lessa, João Paulo Araújo; Delmolin, Guilherme; Santos, Flávia H. (Frontiers in Psychology, 2021)
The COVID-19 outbreak required diverse strategies, such as social distancing and self-isolation, to avoid a healthcare system crisis. However, these measures have been associated with the onset or increase of anxiety and depression symptoms in the population. Music listening was previously shown to regulate emotion, consequently reducing depression symptoms. Since previous studies with Brazilian samples have already shown a high prevalence of depressive symptoms during the first confinement period, the aim of this study was threefold: (i) to compare groups with severe depression symptoms and no depression in what concerns to demographic and socio-economic factors as well as symptoms of anxiety and resilience levels, (ii) to explore changes in music listening daily routine during the confinement measures by both groups (no depression and severe depression), and (iii) to investigate which were the main factors influencing both two groups to music listening during the COVID-19 pandemic. This cross-sectional study included 494 Brazilian respondents aged 18 years and above. Our online survey comprised demographics, socio-economic, and COVID-19 related questionnaires, with questions regarding music listening used during social distancing measures on which the participants rated how much each of the 41 potential reasons for listening to music changed in importance compared to the situation before the pandemic and also the evaluation of anxiety, depression, and resilience levels. The respondents with severe depression were younger and showed higher levels of anxiety symptoms and lower resilience level. Furthermore, they were increasingly likely to listen to music to feel emotionally better with the situation, to feel comfort, to forget problems, to be energetic, to decrease sad feelings, to relax, to cheer up, to forget concerns, to express feelings, to reduce anxiety, to remember better times, to relieve boredom, to mentally stimulate themselves, and to ward off stressful thoughts compared to the participants with no depression. The exploratory factor analysis (FA) identified four types of music listening functions during social distancing measures: negative mood management, cognitive functioning, positive mood management, and physical involvement, in which the participants with severe depression revealed significant differences compared to non-depressed participants for the negative mood management factor, which shows the importance of music listening to regulate their negative emotions. As a conclusion, we can argue that most of our respondents used music listening to cope with and regulate their moods during confinement, especially those who presented with severe depression symptoms.